The Impact of Ethical Leadership on the Service Delivery at Umhlathuze Local Municipality - MAHOHOMA, Tinaye; SIHLANGU, Sipho (PT Keberlanjutan Strategis Indonesia, 2024)
This study aimed to investigate the influence of ethical leadership on service delivery within uMhlathuze Local Municipality, Kwa-Zulu Natal. Despite having established codes of conduct for councilors and officials, instances of unethical behavior persist, eroding public trust and diminishing employee motivation. The detrimental impact of leaders' unethical conduct on the overall workforce diligence is noteworthy. Widespread corruption in numerous global government institutions, particularly in regions with lax policies, underscores the urgent need for ethical leadership in fostering good governance. However, scant research has delved into the specific context of Kwa-Zulu Natal, particularly examining the repercussions of ethical leadership on service delivery at uMhlathuze Local Municipality. To collect data, the researcher employed questionnaires, surveying a carefully chosen sample of 80 respondents from a broader population of 100 within the study area. The obtained field data underwent meticulous analysis using the Statistical Package for Social Sciences (SPSS), Version 29, employing statistical tools such as frequency tables and graphs among others. Implications include recommendations for leadership development programs emphasizing ethical principles and strategies to reinforce a culture of integrity and effective communication.